Gastrointestinal manifestations in children with COVID-19 infection: Retrospective tertiary center experience - Bitar, Rana R; Alattas, Bushra; Azaz, Amer; Rawat, David; Miqdady, Mohamad (Frontiers in Pediatrics, 2022)
Objective: The majority of pediatric severe acute respiratory syndrome coronavirus 2 (COVID-19) cases demonstrate asymptomatic, mild or moderate disease. The main symptoms in children with COVID-19 are respiratory symptoms but some patients develop gastrointestinal symptoms and liver injury. We aim to review gastrointestinal symptoms and liver injury in children with confirmed COVID-19 infection. Method: This is a retrospective case note review of children with positive COVID-19 nasal Polymerase Chain Reaction aged 0-18 years admitted to a tertiary pediatric hospital from March 1st till June 1st 2020. Results: 180 children were identified. Mean age was 5 years (Range: 0.01-17), the majority of patients were school aged (30%). Patients were mainly from East Asia 81 (45%) and Arabs 67 (37%). Gastrointestinal symptoms were encountered in 48 (27%) patients and 8 (4%) patients had only Gastrointestinal symptoms with no associated fever or respiratory symptoms. Liver injury was seen in 57 (32%) patients. Patients with fever and cough were more likely to have gastrointestinal symptoms (P= <0.001 and 0.004 respectively). Fever was more likely to be associated with liver injury (P=0.021). Children with abdominal pain were more likely to have elevated C-Reactive Protein (P=0.037). Patients with diarrhea and vomiting were more likely to have elevated procalcitonin (P=0.034 and 0.002 respectively). Children with Gastrointestinal symptoms were not more likely to be admitted to Pediatric Intensive Care Unit (P=0.57). Conclusion: COVID-19 infection in children can display gastrointestinal symptoms at initial presentation. Additionally, gastrointestinal symptoms can be the only symptoms patients display. We demonstrated that children with gastrointestinal symptoms and liver injury can develop more severe COVID-19 disease and are more likely to have fever, cough, and raised inflammatory markers. Identifying children with gastrointestinal manifestations needs to be part of the initial screening assessment of children.